Development of Chinese herbal medicine for sensorineural hearing loss - Wu, Yunhao; Zhang, Jingwen; Liu, Qiuping; Miao, Zhuang; Chai, Renjie; Chen, Wenyong (Acta pharmaceutica Sinica. B, 2024)
According to the World Health Organization's world report on hearing, nearly 2.5 billion people worldwide will suffer from hearing loss by 2050, which may contribute to a severe impact on individual life quality and national economies. Sensorineural hearing loss (SNHL) occurs commonly as a result of noise exposure, aging, and ototoxic drugs, and is pathologically characterized by the impairment of mechanosensory hair cells of the inner ear, which is mainly triggered by reactive oxygen species accumulation, inflammation, and mitochondrial dysfunction. Though recent advances have been made in understanding the ability of cochlear repair and regeneration, there are still no effective therapeutic drugs for SNHL. Chinese herbal medicine which is widely distributed and easily accessible in China has demonstrated a unique curative effect against SNHL with higher safety and lower cost compared with Western medicine. Herein we present trends in research for Chinese herbal medicine for the treatment of SNHL, and elucidate their molecular mechanisms of action, to pave the way for further research and development of novel effective drugs in this field.